2016
DOI: 10.1002/hbm.23482
|View full text |Cite
|
Sign up to set email alerts
|

Distinct white matter injury associated with medial temporal lobe atrophy in Alzheimer's versus semantic dementia

Abstract: This study aims at further understanding the distinct vulnerability of brain networks in Alzheimer's disease (AD) versus semantic dementia (SD) investigating the white matter injury associated with medial temporal lobe (MTL) atrophy in both conditions. Twenty-six AD patients, twenty-one SD patients, and thirty-nine controls underwent a high-resolution T1-MRI scan allowing to obtain maps of grey matter volume and white matter density. A statistical conjunction approach was used to identify MTL regions showing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…These lesions are associated with neurodegeneration, which is at least partly reflected in gray matter atrophy and glucose hypometabolism measured with structural MRI and positron emission tomography with 18 F-fluorodeoxyglucose ( 18 FDG-PET), respectively. The overlapping alterations in Alzheimer's disease and semantic dementia have been highlighted in previous neuroimaging studies showing common gray matter atrophy to both disorders in medial temporal lobe structures (e.g., hippocampus, amygdala, entorhinal and parahippocampal cortex), lateral temporal and orbitofrontal regions (Chan et al, 2001;Galton et al, 2001;Nestor et al, 2006;Schroeter and Neumann, 2011;La Joie et al, 2013Bejanin et al, 2017). Similarly, both Alzheimer's disease and semantic dementia harbored decreased metabolism in medial and lateral temporal regions (Nestor et al, 2006;Drzezga et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…These lesions are associated with neurodegeneration, which is at least partly reflected in gray matter atrophy and glucose hypometabolism measured with structural MRI and positron emission tomography with 18 F-fluorodeoxyglucose ( 18 FDG-PET), respectively. The overlapping alterations in Alzheimer's disease and semantic dementia have been highlighted in previous neuroimaging studies showing common gray matter atrophy to both disorders in medial temporal lobe structures (e.g., hippocampus, amygdala, entorhinal and parahippocampal cortex), lateral temporal and orbitofrontal regions (Chan et al, 2001;Galton et al, 2001;Nestor et al, 2006;Schroeter and Neumann, 2011;La Joie et al, 2013Bejanin et al, 2017). Similarly, both Alzheimer's disease and semantic dementia harbored decreased metabolism in medial and lateral temporal regions (Nestor et al, 2006;Drzezga et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…In semantic dementia, while the hippocampus is also atrophied, the metabolism of parietal regions is relatively preserved (Nestor et al, 2006;Desgranges et al, 2007;La Joie et al, 2013). A recent study demonstrated that atrophy in the same medial temporal area was associated with distinct white matter injury in Alzheimer's versus semantic dementia, i.e., the cingulum and corpus callosum in the former versus anterior temporal white matter fibers in the latter (Bejanin et al, 2017). Hence, distinct hypometabolism profiles might reflect the involvement of distinct brain networks related to the medial temporal lobe in Alzheimer's disease versus semantic dementia (La Joie et al, 2014;Bejanin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption in WM maturation leads to abnormal brain function correlated with numerous neuropsychological disorders . Furthermore, WM injury occurs in various CNS conditions/diseases, such as attention deficit‐hyperactive disorder, autism, multiple sclerosis, Alzheimer's disease, TBI, and stroke . WM recovery is also related to improved neurological function .…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of research on brain injury has until relatively recently focused on injury to gray matter, the importance of characterizing injury to WM is now being appreciated. Indeed, using diffusion tensor imaging, electron microscopy and/or immunohistological techniques, WM damage has been implicated in a myriad of disorders and diseases, such as traumatic brain injury, attention deficit‐hyperactive disorder, autism, Alzheimer's disease, and stroke . Although these techniques have provided important information about the microstructural changes that occur in WM after injury, less focus has been given to accompanying the functional changes that occur after WM injury.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-echo gradient echo sequences have been already implemented in assessing myelin, axonal and extracellular compartments in white matter architecture and the compartments have shown to be affected by orientation and tissue microstructure (70,73,181). Myelin is the main constituent of white matter and variations in myelin have been associated with neurodegenerative diseases such as Alzheimer's disease, traumatic brain injury and multiple sclerosis (182)(183)(184). Myelin sheath consists of lipids and proteins and they induce specific susceptibilities as lipids have higher magnetic susceptibility than proteins (158,185,186).…”
Section: Chapter 7 Conclusion and Future Directionsmentioning
confidence: 99%